INCREASING COMPANY PERFORMANCE THROUGH CORPORATE SOCIAL RESPONSIBILITY AND GOOD CORPORATE GOVERNANCE - Fredy Olimsar; Muhamad Sarifudin; Edison Hatoguan Manurung; Bambang Rismadi; Uli Wildan Nuryanto (SEAN Institute, 2023)
Corporate responsibility is highly important for society, and in addition, a firm has to have effective corporate governance in order to earn profits. In order to determine if corporate social responsibility and sound corporate governance have an impact on business performance, this study will look for empirical data in this area. There are 79 elements in the criteria table used by Sembiring (2005) to measure CSR. Take a peek at the results of the Corporate Governance Perception Index (CGPI) to get an idea of the metrics used to measure GCG. The Return on Equity is another metric used to assess a company's success. The sample firms for this study were 34 businesses who participated in the CGPI program, declared CSR in annual reports, and were listed on the Indonesia Stock Exchange in the year 2021. The company's annual reports were used as the primary data source for this study. The hypothesis is also tested using multiple linear regression analysis. And according to the study's findings, the CSR and GCG variables have a favorable and substantial impact on corporate performance (ROE).